2012
DOI: 10.1111/j.1708-8208.2010.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Single Implant Treatment in Healing Versus Healed Sites of the Anterior Maxilla: An Aesthetic Evaluation

Abstract: Early and conventional single implant treatment yielded comparable aesthetic outcome. Albeit all treatments had been performed by experienced clinicians and only straightforward cases had been selected, 1 out of 4 cases were aesthetic failures and only a strict minority showed perfection. Research is required on the aesthetic outcome of alternative surgical procedures especially in high-risk patients with a thin-scalloped biotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
159
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(196 citation statements)
references
References 24 publications
29
159
2
Order By: Relevance
“…Cosyn et al in their study showed excellent outcome in about half of their cases 10. This might be due to the difference in the soft tissue type and the technique of implant placement.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Cosyn et al in their study showed excellent outcome in about half of their cases 10. This might be due to the difference in the soft tissue type and the technique of implant placement.…”
Section: Discussionmentioning
confidence: 89%
“…The success of a single implant restoration in the esthetic zone depends mainly on the harmonious integration of the restoration into the patient's overall appearance, especially the peri-implant soft tissue 56. Both subjective (patients' ratings) as well as objective (esthetic scores and indices) assessment of implant esthetics are subject to growing interests,789101112 although there is no universally accepted evaluation criterion yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases the PES-scores were significantly lower with implant-implant interface being in average 7.4 compared to implant- tooth interface; being in average 11.6. However, according to the literature the threshold for clinical acceptability is ranging from PES ≥ 8 (15) and PES over 6 (16). …”
Section: Discussionmentioning
confidence: 99%
“…The PES scale has seven different variables including forms of papillas, soft-tissue level, soft-tissue contour, soft-tissue color, soft-tissue texture, and alveolar process deficiency and it is considered to be an accurate tool for evaluation of aesthetic success of implants placed in anterior maxilla (14). According to previous studies the threshold for clinical acceptability is defined as a PES ≥ 8 (15) or PES over 6 (16). …”
Section: Introductionmentioning
confidence: 99%